Finding the Meaning of Multiculturalism in Tari Bonet: A Christian Religious Education Perspective - Boiliu, Esti Regina; Dirk Roy Kolibu (PT FORMOSA CENDEKIA GLOBAL, 2024)
Tari Bonet, as a cultural heritage of the Dawan ethnic group in East Nusa Tenggara, holds values of unity and kinship that are relevant in building a multicultural society. However, modernization and globalization have shifted the attention of the younger generation from local culture to popular culture, threatening the existence of the values embedded in Tari Bonet. This study aims to explore the meaning of multiculturalism in Tari Bonet from the perspective of Christian Religious Education, using a qualitative approach through ethnographic methods. Data were collected through in-depth interviews with traditional leaders, church leaders, and educators, as well as observations of the performance of Tari Bonet in various social contexts. The research findings indicate that Tari Bonet is not only a symbol of togetherness but also a learning tool for instilling Christian values such as love, tolerance, and respect for diversity. The discussion highlights the role of Christian Religious Education in integrating local cultural values with multicultural principles, while also contributing to cultural preservation efforts. The conclusion of this research emphasizes the importance of synergy between education, the church, and society in preserving Tari Bonet as a medium for shaping the character of the younger generation to appreciate cultural diversity within the framework of Christian faith. This study offers new insights into how local culture can serve as a bridge toward multicultural harmony